An introduction to the verbal behavior (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
This paper is a didactic introductory text to the verbal behavior theme, in a behavioral-analyticperspective. The verbal behavior is characterized as operant behavior, but there are somedifferences between the verbal behavior and the others operant behaviors. Some basics categoriesof verbal behavior are refereed at the end of the paper.